A preliminary comparison of the economics of two water supply alternatives for the city of Fort Collins - Lau, Daniel H., author; Colorado State University, publisher (Colorado State University. Libraries, 1975)
It is the determination of this paper that the Joe Wright Project is more economical than the Installation of Water Meters as a water supply alternative for the city of Fort Collins. Arriving at this conclusion required a brief review of the Joe Wright Project and an investigation of water meters and their effect on water consumption in Fort Collins. This required an examination of such local factors as population, housing and water consumption. It was also necessary to make various projections and assumptions to accomplish this end. This report is intended as a preliminary study of the economics of these projects. The comparisons made here are based solely on a partial (in the sense that many side economic effects of the projects have not been considered) economic analysis. Therefore, financial considerations have been neglected. Specifically, this report compares the cost/AF of water produced or saved by the Joe Wright Project, the Joe Wright Project with one reuse and water meters with three different estimated water use reductions. Based on the analysis completed here, conclusions have been drawn in the hope that they will aid the City in its decision making process.
Also issued as author's thesis.
Series numbering taken from cover.
Keywords: Water-supply -- Colorado -- Fort Collins